2021
DOI: 10.1161/circresaha.120.317104
|View full text |Cite
|
Sign up to set email alerts
|

Clonal Hematopoiesis–Driver DNMT3A Mutations Alter Immune Cells in Heart Failure

Abstract: Rationale: Clonal hematopoiesis (CH) driven by mutations of DNA methyltransferase 3a (DNMT3A) is associated with increased incidence of cardiovascular disease and poor prognosis of patients with chronic heart failure (HF) and aortic stenosis. Although experimental studies suggest that DNMT3A CH-driver mutations may enhance inflammation, specific signatures of inflammatory cells in humans are missing. Objective: To define subsets of immune cells mediating inflammation in humans using single-cell RNA-sequencing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
132
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(148 citation statements)
references
References 27 publications
13
132
3
Order By: Relevance
“…Innate immune cells, such as neutrophils, natural killer cells, and mast cells ( 52 ), have been revealed to participate in the progress of HF through immune inflammation. For instance, monocytes derived from HF patients have higher secreted cytokines (IL-1β, IL-6) and chemokines (CCL3, CCL4), and can stimulate T cell activation ( 53 ). Monocyte-derived macrophages have a pro-inflammation role in cardiovascular diseases ( 49 ).…”
Section: Chronic Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immune cells, such as neutrophils, natural killer cells, and mast cells ( 52 ), have been revealed to participate in the progress of HF through immune inflammation. For instance, monocytes derived from HF patients have higher secreted cytokines (IL-1β, IL-6) and chemokines (CCL3, CCL4), and can stimulate T cell activation ( 53 ). Monocyte-derived macrophages have a pro-inflammation role in cardiovascular diseases ( 49 ).…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…(4) Inflammatory pathways, majorly include the Cytokine-cytokine receptor interaction, TNF signaling, IL-17 signaling, and Toll-like receptor pathways ( Figure 3C ). Additionally, the clonal hematopoiesis pathway is a risk factor of HF enriched in the analysis and may be related to immune inflammation ( 53 , 159 ). (5) Other structural remodeling in addition to hypertrophy, such as fibrosis and amyloidosis.…”
Section: Link Between Heart Failure and Comorbiditiesmentioning
confidence: 99%
“…Diverse mediators of innate and adaptive immunity have been described to be modulated by the occurrence of specific CH-associated somatic mutations [65,66]. Not only cellular components of the myeloid lineage like monocytes/macrophages [56,[67][68][69][70], mast cells [71], neutrophils [72], but also lymphatic cells [73][74][75][76][77] can exert altered function.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the transcriptome profiles of peripheral blood mononuclear cells in N = 6 HF patients with DNMT3A CH-driver mutation and N = 4 HF patients without DNMT3A mutation were analyzed by single-cell RNA sequencing.This study found that circulating monocytes and T cells of patients with HF harboring clonal hematopoiesis-driver mutations in DNMT3A exhibit a highly inflamed transcriptome, which may result in the aggravation of chronic HF. [27].…”
Section: Relationship Between Chip and Risk Of Cardiovascular Disease In Humansmentioning
confidence: 99%
“…These results suggest that TET2 deficiency may impair inflammatory regression and innate immune response [65]. In 2020, Wesley T Abplanalp and his colleagues using singlecell RNA-sequencing revealed that circulating monocytes and T-cells of HF patients harboring CH-driver mutations in DNMT3A exhibited a highly inflamed transcriptome in humans [66]. It has been demonstrated for the first time that DNMT3A mutation induces activation of inflammatory signals of different immune cells in humans.…”
Section: Inflammation As a Consequence Of Clonal Hematopoiesismentioning
confidence: 99%